Assessing the Impact of Government Policy on University Admissions in Nigeria: A Study of Admission Capacity and Policy Implementation (2009 – 2018) - Temitope, ATTE, Priscilla; Hauwa , IMAM (International Journal of Educational Management, 2025)
Prior to Nigeria's independence, the colonial masters created universities primarily with the purpose of educating and providing highly qualified labor to take over the management of government departments and businesses and to foster state growth. Since independence, these principles and objectives for founding and managing universities have mostly remained the same without significant revision, particularly in public universities. The impact of government policy on higher education regarding university admission in Nigeria is examined in this study. To achieve this, the study identifies government policies on higher education and admissions and evaluates them in light of contemporary circumstances, particularly as they relate to university admissions. Major rules on university admissions are covered in the pertinent literature/documents examined and used for this paper, a topic that has previously gotten less attention in studies on university education in Nigeria. Therefore, in order to close the knowledge gap, this research focus on analyzing the government's policy on Nigerian university admissions' carrying capacity in order to assess how the institutions have been managing student admissions. As the only research instrument, interviews were used in a qualitative approach. The results show that the carrying capacity of the universities has been exceeded because it is far lower than the number of applicants admitted each year, rendering admissions procedures that could improve the caliber of graduates generated ineffective.